Analisis Kreativitas Mengajar Guru Terhadap Daya Serap Peserta Didik - Ismi Andani Maruhawa; Asni Junita Zega; Agnes Renostini Harefa (Peneliti.net, 2023)
This study aims to analyze the teacher's teaching creativity on the absorption of students. The creativity of a teacher in teaching is the main factor in supporting the success of the learning process. Creative teachers are able to develop their abilities, new ideas and also new ways of teaching. To develop teaching creativity, a teacher must broaden his knowledge and skills in applying methods, strategies, models, learning media and making variations in the learning process. This study uses a qualitative descriptive method with data collection using observation, interviews and also literature studies.